Human Capital Migration: A Longitudinal Perspective. (3rd October 2018) - Kooiman, Niels; Latten, Jan; Bontje, Marco
Abstract: Based on micro‐level administrative data this paper aims to identify the role of internal migration in shaping regional and inter‐urban contrasts in human capital stocks in the Netherlands. We follow birth cohort 1979 from age 16 until age 35 and compare spatial trajectories between university graduates(‐to‐be) and their lower educated peers. We conclude that, in a context of dominating rural‐to‐urban migration flows, the highest educated(‐to‐be) are more than others attracted to metropolitan core areas and the Randstad. Second, we aim to test whether this urban preference may be prompted by spatial variation in socio‐economic progression by comparing changes in the relative wage position of employees in different spatial settings. Metropolitan settings and the Randstad in general are found to function more than other regions as socio‐economic escalators during the first phase of the labour career. However, these effects appear to be equal among educational groups.